Managing Security with Snort and IDS Tools - Cox, Kerry J. (O'Reilly, 2011)
This practical guide to managing network security covers reliable methods for detecting network intruders, from using simple packet sniffers to more sophisticated IDS (Intrusion Detection Systems) applications and the GUI interfaces for managing them. A comprehensive resource for monitoring illegal entry attempts, Managing Security with Snort and IDS Tools provides step-by-step instructions on getting up and running with Snort 2.1, and how to shut down and secure workstations, servers, firewalls, routers, sensors and other network devices.